SPEECH STYLE USED IN JOKO WIDODO’S SPEECH - Gawa, Damsianus; Sama, Gratiana; Doi, Maksimilianus (Lantern: Journal of Language and Literature, 2022)
The current study aimed at finding out the types of speech style in Joko Widodo’s speech using the theory of Martin Joos, (1967). The study was a qualitative descriptive method. The data taken were Joko Widodo’s speeches in two different events, mainly at MPR Annual Meeting and IMF annual meeting. Due to fact that the speeches were in form of utterances gained from two videos and its scripts as referential source of data, this study referred to a research by documentation technique. This technique was administered to gather all speech events gained by reading the scripts to find out Joko Widodo’s speech style. The results of this study indicate that there are five types of speech style found in Joko Widodo’s speeches, namely frozen style, consultative style, casual style, and intimate style. In two different speeches, Joko Wido do tends to mostly use frozen style in his speech here by Joko Widodo speech in very formal situation in his speeches than other types of speech style.